SAT0447 Validation of the 2017 acr/eular classification criteria of systemic lupus erythematosus. (12th June 2018) - Suda, M.; Yanaoka, H.; Rokutanda, R.; Tsuda, T.; Kishimoto, M.; Yamaguchi, K.; Okada, M.
Abstract : Background: Two major classification criteria have been used in the clinical trials of systemic lupus erythematosus (SLE). One is American College of Rheumatology (ACR) criteria first developed in 1982 and revised in 1997 (1997 criteria) 1, and the other is Systemic Lupus International Collaborating Clinics (SLICC) criteria developed in 2012 (2012 criteria) 2 . In the ACR annual meeting on November 2017, the new classification criteria of SLE (2017 criteria) were proposed, aiming for better specificity and sensitivity. They were made based on the agreement of expert panel 3, and have not been validated in the real-world practice. Objectives: The objective of the study is to evaluate the sensitivity of 2017 criteria when applied to real SLE cases. Methods: We retrospectively reviewed the electronic medical record of the consecutive 100 patients who visited St. Luke's International Hospital, a tertiary care centre in Tokyo, Japan, searching back from November 13, 2017. Patients were included if they are clinically diagnosed as having SLE with board-certified doctors, and excluded if they complicated with other autoimmune disease or if they are under 18-year-old. Each patient was evaluated if he or she satisfied the 1997, 2012, or 2017 criteria. Results: Among the 100 cases, 9 were male and 91 were female, with wide range of age; 18–88 mean 44.5-year-old). Asian accounted for 98%, with Hispanic 1%, and Caucasian 1%., The sensitivity of 1997, 2012 2017 criteria are, 97%, 99%, 87% respectively. The positivity rate of each domain in the 2017 criteria was shown in table 1. The total score that the patients got in the 2017 criteria ranged from 12 to 44 (mean: 27.3). All the cases who were classified as non-SLE in the 2017 criteria had anti-nuclear antibody (ANA) <80; all of them scored more than 10 points. Abbreviations: ACLE, acute cutaneous lupus erythematosus; ANA, anti-nuclear antibody; anti-CL, anti-cardiolipin antibody; DLE, discoid lupus erythematosus; N/A, not available; SCLE, Sub-acute cutaneous lupus erythematosus; SLE, systemic lupus erythematosus. Conclusions: 2017 criteria for SLE accomplished modestly high sensitivity in the real-world practice, but not as high as 1997 and 2012 criteria. They possibly miss-classify the real SLE cases as non-SLE, especially if patients have low titer (<80) of ANA. References: [1] Hochberg MC, et al. Updating the American College of Rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum1997Sep;40(9):1725. [2] Petri, Michelle, et al. "Derivation and validation of the Systemic Lupus International Collaborating Clinics classification criteria for systemic lupus erythematosus."Arthritis & Rheumatology2012;64(8):2677–2686. [3] http://acrabstracts.org/abstract/use-of-nominal-group-technique-to-determine-candidate-items-for-sle-classification-criteria-development/ Disclosure of Interest: None declared